NEU1 Regulates Mitochondrial Energy Metabolism and Oxidative Stress Post-myocardial Infarction in Mice via the SIRT1/PGC-1 Alpha Axis - Guo, Zhen; Fan, Di; Liu, Fang-Yuan; Ma, Shu-Qing; An, Peng; Yang, Dan; Wang, Min-Yu; Yang, Zheng; Tang, Qi-Zhu (Frontiers in Cardiovascular Medicine, 2022)
Objective Neuraminidase 1 (NEU1) participates in the response to multiple receptor signals and regulates various cellular metabolic behaviors. Importantly, it is closely related to the occurrence and progression of cardiovascular diseases. Because ischemic heart disease is often accompanied by impaired mitochondrial energy metabolism and oxidative stress. The purpose of this study was to investigate the functions and possible mechanisms of NEU1 in myocardial remodeling and mitochondrial metabolism induced by myocardial infarction (MI). Methods In this study, the MI-induced mouse mode, hypoxia-treated H9C2 cells model, and hypoxia-treated neonatal rat cardiomyocytes (NRCMs) model were constructed. Echocardiography and histological analysis were adopted to evaluate the morphology and function of the heart at the whole heart level. Western blot was adopted to determine the related expression level of signaling pathway proteins and mitochondria. Mitochondrial energy metabolism and oxidative stress were detected by various testing kits. Results Neuraminidase 1 was markedly upregulated in MI cardiac tissue. Cardiomyocyte-specific NEU1 deficiency restored cardiac function, cardiac hypertrophy, and myocardial interstitial fibrosis. What is more, cardiomyocyte-specific NEU1 deficiency inhibited mitochondrial dysfunction and oxidative stress induced by MI. Further experiments found that the sirtuin-1/peroxisome proliferator-activated receptor γ coactivator α (SIRT1/PGC-1α) protein level in MI myocardium was down-regulated, which was closely related to the above-mentioned mitochondrial changes. Cardiomyocyte-specific NEU1 deficiency increased the expression of SIRT1, PGC-1α, and mitochondrial transcription factor A (TFAM); which improved mitochondrial metabolism and oxidative stress. Inhibition of SIRT1 activity or PGC-1α activity eliminated the beneficial effects of cardiomyocyte-specific NEU1 deficiency. PGC-1α knockout mice experiments verified that NEU1 inhibition restored cardiac function induced by MI through SIRT1/PGC-1α signaling pathway. Conclusion Cardiomyocyte-specific NEU1 deficiency can alleviate MI-induced myocardial remodeling, oxidative stress, and mitochondrial energy metabolism disorder. In terms of mechanism, the specific deletion of NEU1 may play a role by enhancing the SIRT1/PGC-1α signaling pathway. Therefore, cardiomyocyte-specific NEU1 may provide an alternative treatment strategy for heart failure post-MI.